Taxonomic Descriptions and Phylogenetic Placement of Aspergillus subalbidus isolated from a Paper Wasp Nest - Weerasinghe, Gayana O.; Bhunjun, Chitrabhanu S.; Phukhamsakda, Chayanard; Thakshila, Subasingha A.d.; Hyde, Kevin D.; Al-Otibi, Fatimah (Phytotaxa, 2025)
Aspergillus is a widely distributed genus occurring on diverse hosts and substrates. During a survey in Chiang Rai Province, Thailand, an Aspergillus species was found associated with a decaying nest of paper wasp (Polistes sp.). According to the morphological characterization and multi-locus phylogenetic analyses based on internal transcribed spacer (ITS) region, β-tubulin (BenA), calmodulin (CaM), and the second largest subunit of RNA polymerase II (RPB2) genes, we identified our strain as A. subalbidus (MFLUCC 25-0297). Phylogenetic analysis placed the isolate (MFLUCC 25-0297) within Aspergillus section Candidi. Our isolate exhibits high sequence similarity and morphological characters consistent with the type strain of A. subalbidus. This is the first record of Aspergillus subalbidus from decaying paper wasp nests. This study expands the knowledge of host association and ecological distribution of A. subalbidus suggesting its potential role in the decomposition of insect-associated lignocellulosic substrates. Further investigations are required to assess the enzymatic capabilities of these species and their ecological interactions with social insects.